More losses than gains? Distribution models predict species-specific shifts in climatic suitability for European beech forest herbs under climate change - Kermavnar, Janez; Kutnar, Lado; Marinšek, Aleksander (Frontiers in Forests and Global Change, 2023)
Introduction Herbaceous plant species constitute an essential element of the flora of European beech (Fagus sylvatica) forests. There is increasing evidence that rapidly changing climate is likely to modify the spatial distribution of plant species. However, we lack understanding of the impact that climate change might have on beech forest herbs across the European continent. We investigated the possible effects of predicted increasing rates of global warming and altered precipitation regimes on 71 forest herbs closely associated with beech forests, but with varying biogeographic and climatic niche attributes. Methods By using a total of 394,502 occurrence records and an ensemble of species distribution models (SDMs), we quantified the potential current distribution and future (2061-2080) range shifts in climatic suitability (expressed as occurrence probability, OP) according to two climate change scenarios (moderate SSP2-4.5 and severe SSP5-8.5). Results Overall, precipitation of the warmest quarter and temperature seasonality were the most influential predictors in shaping current distribution patterns. For SSP5-8.5 scenario, all studied species experienced significant reductions (52.9% on average) in the total size of highly suitable areas (OP >0.75). However, the magnitude and directions of changes in the climatic suitability were highly species-specific; few species might even increase OP in the future, particularly in case of SSP2-4.5 scenario. The SDMs revealed the most substantial decline of climatic suitability at the trailing edges in southern Europe. We found that climatic suitability is predicted to show unidirectional northward shift and to move toward higher elevations. The gain/loss ratio was generally higher for narrow-ranged species compared to widespread taxa. Discussion Our findings are contextualized with regards to potential confounding factors (dispersal limitation, microclimatic buffering) that may mitigate or accelerate climate change impacts. Given the low long-distance migration ability, many beech forest herbs are unlikely to track the velocity with which macroclimatic isotherms are moving toward higher latitudes, making this species group particularly vulnerable to climate change.